Biological control of the invasive Thrips parvispinus (Karny) (Thysanoptera: Thripidae) using entomopathogenic nematodes - Vargas, German; Ataide, Livia M. S.; Velazquez-Hernandez, Yisell; De Giosa, Marcello; Revynthi, Alexandra M. (Frontiers in Agronomy, 2026)
Thrips parvispinus (Karny) (Thysanoptera: Thripidae) is an invasive pest increasingly affecting ornamental production in Florida, with a rapid expansion in North America, Europe, and Africa. Current management relies heavily on chemical control, highlighting the need for more sustainable alternatives, such as entomopathogenic nematodes (EPNs). We evaluated six EPN species (Heterorhabditis bacteriophora, Heterorhabditis indica, Steinernema carpocapsae, Steinernema riobrave, Steinernema feltiae, and Steinernema kraussei) under laboratory conditions, using a rate of 200 IJ/cm2. Subsequently, the four best-performing species (H. bacteriophora, H. indica, S. carpocapsae, and S. riobrave) were further tested under greenhouse conditions using mandevilla plants and soil applications at a rate of 100 IJ/cm2. Trials were conducted at 27 °C, reflecting the average temperatures of the ornamental growing and shipping seasons in southern Florida, while applications targeted the prepupal and pupal soil-dwelling stages of the pest. Observations of the surviving adults were recorded. In laboratory trials, the application of H. bacteriophora, S. riobrave, H. indica, and S. carpocapsae reduced the recovery adult thrips by 20 - 36% compared to controls. Greenhouse trials demonstrated reductions in all treatments where EPNs were applied, with reductions of up to 60% in adult recovery in S. riobrave and S. carpocapsae. Environmental factors, including warm temperatures and low substrate moisture, helped explain the EPN performance, favoring warm-adapted and desiccation-tolerant species. This is the first report demonstrating EPN efficacy against T. parvispinus, suggesting its potential for integration as an alternative tool within IPM programs.